Exploring the Biological Potentials of Cissus quadrangularis Linn. with Special Reference Exploiting the Anticancer and Antibacterial Activities - P. Samuel; J. Augostriena; T. Selvarathinam; D. N. P. Sudarmani (Innovations in Microbiology and Biotechnology Vol. 4, 2022)
The decisive aim of the work was focused on unzipping the constructional use of the biopotentials of Cissus quadrangularis Linn. which may pave the way for the identification of novel drug leads for life threatening and challenging diseases. The plant was collected from Shenbagathoppu Reserved Forest which is located in southern part of Tamil Nadu, India. Three diverse solvents like ethyl acetate, hexane and water were used for extraction. Phytochemical fingerprint of the extracts were analyzed using GC-MS. Aqueous, Ethyl acetate and Hexane extract decoctions showed 37, 43 and 38 versatile compounds respectively. In the present study, Anticancer and Antibacterial study was carried out to evaluate the biological potentials of compounds fractionated form Cissus quadrangularis Linn. Among the three extracts, IC50 value of ethyl acetate extract was found to be the least which was 1.27 \(μ\)g/ml. IC50 value of hexane extract and aqueous was 4.12 \(μ\)g/ml and 4.46 \(μ\)g/ml respectively. Antibacterial activity revealed that increase in concentration of extract showed an increase zone of inhibition, maximum zone of inhibition was observed as 14 mm against Escherichia coli in ethyl acetate extract and it was 9mm against Escherichia coli in hexane extract.